2022
DOI: 10.3389/feart.2022.864189
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Characterization for Pore Connectivity, Pore Wettability, and Shale Oil Mobility of Terrestrial Shale With Different Lithofacies—A Case Study of the Jurassic Lianggaoshan Formation in the Southeast Sichuan Basin of the Upper Yangtze Region in Southern China

Abstract: Some major hydrocarbon-bearing basins are rich in shale with terrestrial facies in China, which may provide abundant terrestrial shale oil and gas resources. This work studied the Jurassic Lianggaoshan Formation in the Southeast Sichuan Basin of the upper Yangtze Region. Core samples were chosen for the total organic carbon content and mineral composition analyses to classify shale lithofacies. Afterward, pore connectivity, pore wettability, and shale oil mobility with different lithofacies were characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Comprehensie histogram of sampling depth, analysis and test results of the samples, and lithofacies division results in Member I and Member II of Well TYX. Modified from references (Liu W. et al, 2021;Wei et al, 2021;Zhang et al, 2022b). See Figure 1 for the well location.…”
Section: Figurementioning
confidence: 98%
See 2 more Smart Citations
“…Comprehensie histogram of sampling depth, analysis and test results of the samples, and lithofacies division results in Member I and Member II of Well TYX. Modified from references (Liu W. et al, 2021;Wei et al, 2021;Zhang et al, 2022b). See Figure 1 for the well location.…”
Section: Figurementioning
confidence: 98%
“…Location of the Fuling block and the distribution of TYX well sites in the southeast of Sichuan Basin, South China. Modified from references (Guo et al, 2016;Guo et al, 2017;Liu W. et al, 2021;Wei et al, 2021;Zhang et al, 2022b).…”
Section: Fib-sem Observationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the natural gas geochemistry parameters (Qin et al, 2006;Xu et al, 2017;Qin et al, 2018), the C 1 /C 2 values go up with the increase of maturity or migration distance (Ye et al, 2017a), while the iC 4 /nC 4 values go down with the increase of maturity but rise with the increase of migration distance in the case of loose reservoirs. However, they descend with the increase of migration distance in the case of tight reservoirs (Li et al, 2002;Zhang et al, 2022a). In addition, δ 13 C 1 values rise with the increase of maturity (Liu et al, 2007;Liu et al, 2007;Liu, 2021).…”
Section: Natural Gas-filling Periodsmentioning
confidence: 99%
“…Gas-bearing characteristics is an important index to evaluate whether shale gas is worthy of exploration and development value. Understanding the gas bearing characteristics is the prerequisite for the next work (Daniel and Bustin, 2009;Wang and Gale, 2009;Huang et al, 2020;Zhang et al, 2022d;Zhang et al, 2022e). Based on the field gas content test of the carbonaceous shale samples from several wells in study area, it is found that Leping Formation carbonaceous shale has a high shale gas content.…”
Section: Gas-bearing Characteristicsmentioning
confidence: 99%